2016
DOI: 10.3354/dao03044
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of common carp and sunfish to a strain of Francisella noatunensis subsp. orientalis in a challenge experiment

Abstract: Francisellosis, an emerging disease in many fish species, can cause high mortality in affected populations. Here we investigated the susceptibility of common carp Cyprinus carpio and sunfish Lepomis gibbosus to Francisella noatunensis subsp. orientalis (Fno), and possible transmission of the bacteria between the 2 fish species. In a challenge experiment, 3 groups of each species were injected intraperitoneally (IP) with 3 different doses of an Fno strain no. 9449 of the Norwegian Veterinary Institute, recovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Melanomacrophage aggregates seen in high numbers inside granulomas in Asian seabass tissues (c, d). Scale bar = 50 μm [Colour figure can be viewed at wileyonlinelibrary.com] (Lewisch, Menanteau-Ledouble, Tichy, & El-Matbouli, 2016), and common carp and catfish did not die even when injected with a high dose (Dong et al, 2016). Different species of tilapia show different levels of susceptibility (Klinger-Bowen et al, 2016).…”
Section: F I G U R Ementioning
confidence: 99%
“…Melanomacrophage aggregates seen in high numbers inside granulomas in Asian seabass tissues (c, d). Scale bar = 50 μm [Colour figure can be viewed at wileyonlinelibrary.com] (Lewisch, Menanteau-Ledouble, Tichy, & El-Matbouli, 2016), and common carp and catfish did not die even when injected with a high dose (Dong et al, 2016). Different species of tilapia show different levels of susceptibility (Klinger-Bowen et al, 2016).…”
Section: F I G U R Ementioning
confidence: 99%
“…The route of F. orientalis introduction to the public display system remains uncertain. Previous challenge experiment results indicated that Pumpkinseed Lepomis gibbosus are susceptible to F. orientalis infection, so the possibility of transmission through frozen sunfish diets should be considered (Lewisch et al 2016). Alternatively, F. orientalis could have been introduced into the system through an infected wild-caught or aquaculture-raised fish.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the relevance of ornamental cichlids is not counterbalanced by literature references regarding pathologic conditions, with only a limited amount of papers being available [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%